81 Yeast Cell Wall Mannan-Rich Fraction Reduces Growth and Enhances Antibiotic Sensitivity of Resistant ESBL-Producing E. coli. (10th April 2018) - Smith, H; Jacques, K; Murphy, R
Abstract: Intestinal infection with enterotoxigenic Escherichia coli (ETEC) is an important disease in swine resulting in significant economic losses. The ETEC causing neonatal colibacillosis mostly carry fimbriae and these fimbriae adhere to specific receptors on porcine intestinal brush border epithelial cells starting the process of enteric infection. Mannan rich fractions, extracted from yeast, structurally resemble the receptor sites coating the intestinal epithelium to which intestinal pathogens like ETEC's adhere. These oligosaccharides act as molecular decoys which can competitively inhibit adherence of pathogens to the intestinal epithelium. The objective of this study was to determine if a commercial mannan rich fraction (MRF, Actigen) extracted from the yeast Saccharomyces cerevisiae could reduce adherence of a number of ETEC strains to intestinal porcine epithelial cells (IPEC-J2) in-vitro . Briefly, IPEC J2 cells (2*10 4 passage 10-18) were cultured on 6 well plates using CO2 independent medium pH 6.8. The adhesion test consisted of incubation of the MRF (16mg/mL) with the bacteria, this mixture was then added to the IPEC-J2 cell monolayer followed by 30 min incubation (at 37 ◦ C and 5% of CO2 ) with the cell monolayer. After washing the IPEC-J2 lysates were collected, which consisted of bacteria which adhered to the cells and invaded the cells, and plated on plate count agar, after overnight culturing colonies were counted, the adhesion test was repeated on three different days for each strain of E.coli . Adhesion tests with three different strains of E.coli were performed; E.coli 17076, 10674 and 10964 each of which carried fimbrae. MRF shows a clear ability to reduce the number of E.coli cells which adhered to the IPEC-J2 cells. In the case of strain 17076 the adherent cells decreased from 1.51x10 6 CFU in the control untreated IPEC cells to 2.19 x10 5 with the Actigen treatment this represents a significant seven fold reduction in attachment p< 0.05. In the case of strain 10674 the adherent cells decreased from 1.43 x10 6 CFU in the control untreated IPEC cells to 5.28 x10 4 with the Actigen treatment this represents a 28 fold reduction in attachment of E.coli P< 0.05 and for strain 10964 a fivefold reduction in attachment of E.coli to the IPCE cells was noted P<0.05. These results indicate that in this study yeast mannan rich fraction (Actigen) reduced E.coli adherence to intestinal cells in-vitro . In addition these data suggests that inclusion of MRF in the diets of pigs could potentially support functional activity against E.coli infection.